Peran Dinas Sosial Dalam Menangani Kekerasan Seksual Terhadap Anak Di Kabupaten Nagan Raya - Reva Alen Nauri; Sudarman Sudarmawan (Journal of Social Politics and Governance (JSPG), 2022)
This study aims to determine how the role of the Social Service in dealing with sexual violence against children in Nagan Raya district.  This study uses a descriptive qualitative research method.  The informants in this study amounted to 3 (three) informants.  The theory used in this research is role theory with indicators of providing assistance, recovering trauma, as a broker (liaison), as an advocate, as a motivator, and providing legal assistance.  The results in this study indicate that the role of social services in dealing with sexual violence in Nagan Raya district has been carried out well.  In this study, the obstacles faced by social services in dealing with sexual violence were the lack of budget and the unavailability of safe houses.  The Social Service is able to reduce and overcome the negative impacts caused by acts of sexual violence experienced by children such as trauma, inferiority, depression.